Effect of statins combined with PCSK9 inhibitors on the prognosis of patients with acute coronary syndromes after interventional therapy: The role of PCSK9 in ACS - Shi, Lu; Ye, Zekang; Gu, Qian; Li, Yong (Cellular and Molecular Biology, 2023)
Acute coronary syndromes (ACS) are a leading cause of morbidity and mortality worldwide. It has been clinically confirmed percutaneous coronary intervention (PCI) can alleviate the symptoms of ACS, but there are still some patients with slow blood flow or no-reflow after surgery, which has adverse effects on the prognosis of patients. This study aimed to investigate the effect of statins combined with PCSK9 inhibitors on the prognosis of patients with ACS after interventional therapy. A total of 208 ACS patients treated in our hospital from January 2021 to December 2022 were separated into observation and control groups. Patients in the control group received oral rosuvastatin 20 mg/ day. Patients in the observation group received PCSK9 inhibitor elozumab (Repatha) 140 mg, subcutaneously injected twice a week. The levels of inflammatory factors, cardiac function indexes, clinical effectiveness rate, adverse events, and complications were compared before and after treatment. After 1 week of treatment and 4 weeks of follow-up, the levels of inflammatory indicators in the observation group declined relative to the control group (P < 0.05 and P < 0.01). After 4 weeks, LVEF in the observation group was elevated in comparison to the control group, while LVEDD in the observation group declined compared to the control group (P < 0.05). The incidence of adverse events after treatment in the observation group declined relative to the control group (P < 0.05). The incidence of complications in the observation group declined in contrast to the control group (P < 0.05). Statins combined with PCSK9 inhibitors significantly reduce LDL-C levels in ACS patients undergoing PCI without increasing cardiovascular events or major adverse clinical effects.